CLUSTERING OF OBJECTS USING THE DBSCAN ALGORITHM - Shavkat Fayzullayevich Madraximov; Sherzod Dilmurodovich Dilmurodov; Fayzulla Yusupovich Shodiyev; Munisa Davronova (Modern American Journals, 2025)
This article discusses the solution to the problem of identifying complex hidden relationships between varieties by clustering using the DBSCAN algorithm, dividing the features of soft wheat varieties into groups (reflecting the growth and development of the wheat plant, components of fertility and fertility, reflecting the quality of the grain).
Keywords: DBSCAN, legality, K-means,  − neighboured, cluster, root object, boundary object, noise object, MinPts.